Childhood poverty, immune cell aging, and African Americans' insulin resistance: A prospective study. Issue 5 (21st May 2022) - Barton, Allen W.; Yu, Tianyi; Gong, Qiujie; Miller, Gregory E.; Chen, Edith; Brody, Gene H.
Abstract: The present study investigated developmental pathways that can contribute to chronic disease among rural African Americans. With a sample of 342 African American youth (59% female) from the southeastern United States followed for nearly two decades (2001–2019), we examined the prospective association between family poverty during adolescence (ages 11–18) and insulin resistance (IR) in young adulthood (ages 25–29) as well as underlying biological and psychosocial mechanisms. Results indicated family poverty during adolescence forecast higher levels of IR in young adulthood, with accelerated immune cell aging at age 20 partially mediating this association. Serial mediational models confirmed the hypothesized pathway linking family poverty, perceived life chances, cellular aging, and IR. Findings provide empirical support for theorized developmental precursors of chronic disease.